A STUDY ON READING STRATEGIES USED BY 11th GRADE STUDENTS OF SMA BRAWIJAYA SMART SCHOOL UNIVERSITAS BRAWIJAYA MALANG - HERLYNA, ITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: reading strategies, science program and social program, Survey of Reading Strategies (SORS). There are four language performances which are important  in academicprocess, including speaking, writing, reading, and listening. Those languageperformances are important, but reading is essential one and the most  important skill, especially for L2 learners in mastering academic process. In reading L2, Indonesian students get difficulties because foreign languge is different with their mother tounge. Therefore, reading strategies are needed. This study is aimed at finding out the kinds of reading strategies, the most frequently used reading strategy, and the significant difference of reading strategy between science and social students of SMA Brawijaya Smart School Universitas Brawijaya Malang.This study used descriptive quantitative approach dealing with survey research. The data of the study were collected by using questionnaire named Survey of Reading Strategies (SORS) designed by Mokhtari and Sheorey (2002). The sample of this study are the students of XI IPA 1 and XI IPS 2.The results revealed that the use of overall reading strategies for science fell into high level. It means that science students usually used reading strategiesduring reading process, it might be very important strategies for science students. While, the use of overall reading strategies for social fell into medium, means that they sometimes used reading strategies during reading process. Social students consider that reading strategies are important to do during reading process. Specifically, both science and social favored problem solving strategies as the most usage, followed by support reading strategies and global reading strategies. In addition, there is significant difference of reading strategies between science and social students.Regarding the importance of reading strategy, the students have to applyreading strategies in reading process, so they will get a lot of knowledge fromreading and they can compete in international school. Besides, the teacher canhelp them understand more about the importance of reading strategy. For the next researchers, they should be find the factor that make the participants use different strategies in reading process.